Inequality and mobility of household incomes in Europe: Evidence from the ECHP - Gerhard Riener (Institute for Advanced Studies (IHS), 2006)
In this paper I want to shed light on two aspects of income mobility: relative total income mobility using the estimator by Fields and Ok [1999] and equalization of long-run incomes measured by the index of Fields [2004]. The cross country comparison shows a negative relationship between total relative mobility and long-run income equalization, this results is contrary to the intuition given by Shorrocks [1978a] who stated, that higher relative mobility will cause higher equalization of incomes when the accounting period is extended.
Keywords: J30; D63; 330; income distribution; economic mobility; inequality; Verteilungsgerechtigkeit; Volkswirtschaft; Europa